A Synchronization Algorithm for Distributed Time Stepped Simulation: An Application to Wargame - Grover, Pooja (My University, 2007)
An overview of technologies concerned with distributing the execution of simulation programs across multiple processors is presented. Here, particular emphasis is placed on discrete event simulations. The main focus of this research work is on time management, a central issue concerning the synchronization of computations on different processors. Time management algorithms broadly fall into two categories, termed conservative and optimistic synchronization. A survey of both conservative and optimistic algorithms is presented focusing on fundamental principles and mechanisms. Time management in the HLA is discussed as a means to illustrate how this standard supports both approaches to synchronization. Finally a new time synchronization approach is suggested and then implemented. This approach is specifically meant for time stepped simulations. Institute for System Studies and Analyses (ISSA) has developed software’s which provide a computerized combat training environment, designed to train commanders and staff in combined arms environment for realistic battlefield conditions. The thesis work will provide a survey of the various time synchronization algorithms and will thus provide solution for synchronization of time among various distributed simulation processes.
Keywords: Time Stepped Simulation; Wargame; Federate; Sinchronoization